Probiotics and constant temperature's impacts on asian seabass Lates calcarifer fry growth, survival, and health - Haryanti; Sembiring Sari Budi Moria; Muzaki Ahmad; Permana Gusti Ngurah; Sugama Ketut (E3S Web of Conferences, 2023)
This study is conducted to provide information on the effect of temperature and incorporation of probiotics on the growth, survival, and health of Asian seabass L. calcarifer fry. A constant temperature of 30 ± 0.5 °C was applied for larval rearing of Asian bass combined with probiotic supplements (Alteromonas sp. BY-9 and Bacillus cereus BC). Containers for larval rearing were using a polycarbonate tank with a volume of 200 L. The treatments applied were (A) application of temperature and probiotics and (B) without application of temperature and probiotics (Control). Each treatment was repeated six times, and the rearing tanks were positioned in a large tank to form a water bath system. The results of growth of fry during rearing with constant temperature and supplemented of probiotics (A) and control (B) showed different growth profiles. The time needed to reach a body length of 2.5 cm in (A) treatment was only 37 days after hatching, while in (B) treatment, it took two days longer, which was 39 days. In (A) treatment, immunity increased in all target genes by relatively high multiples expression (5 times in CAT, 3-30 times in HSP-70, and 1 -1.6 times in SOD)